EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DENGAN PENDEKATAN OPEN-ENDED PADA PEMBELAJARAN MATEMATIKA DITINJAU DARI ADVERSITY QUOTIENTS (AQ) SISWA SMA NEGERI DI KOTA MATARAM - Azizah, Eka Nur; Usodo, Budi; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2013)
Abstract:The objectives of this research are to investigate: (1) which of the cooperative learning model of NHT type with open-ended approach, the cooperative learning models of NHTtype, and the model of conventional results in a better learning achievement in mathematics of the students; (2) which of the types of climbers, the campers, and the quittersresults in a better learning achievement in mathematics; (3) for each category of AQ of the students, which one results in better achievement in mathematics, cooperative learning model of NHT type with open-ended approach, the cooperative learning model of NHTtype, and the model of conventional; and (4) for each learning model, which one results in better achievement in mathematics, students who have climbers type, campers, or quitters.The type of this research was a quasi-experimental with research design which used factorial 3 x 3.The population of this research was the first grade (Class Ten) of Senior High Schools in Mataram. The sample of this research was 9 classes consisted of 3 experimental classes I, 3 experimental classes II, and 3 control classes. This research used stratified cluster random sampling technique.The results of the research are as follows: (1) the cooperative learning models of NHT type with open-ended approach results in a better studentsâ mathematics learning achievement than cooperative learning model of NHTand the model of conventional, and the cooperative learning model of NHTtype results in a better studentsâ mathematics learning achievement than the model of conventional; (2) studentsâ mathematics learning achievementwith the climbers type of learning gives the same mathematics achievement as the campers type, studentsâ mathematics learning achievement with the campers type of learning gives the same mathematics achievement as the quitters type, and studentsâ mathematics learning achievement with the climbers type of learning results in a better achievement than the learning achievement of the students with the quitters type; (3) for each category of AQ of the students (climbers, campers, and quitters), cooperative learning model of NHT type with open-ended approach results in a better studentsâ mathematics learning achievement than cooperative learning model of NHTand the model of conventional, and the cooperative learning model of NHTtype results in a better studentsâ mathematics learning achievement than conventional type; (4) for each learning model (NHT type with open-ended approach, NHT type, and conventional), studentsâ mathematics learning achievement with the climbers type of learning gives the same mathematics achievement as the campers type, and studentsâ mathematics learning achievement with the campers type of learning gives the same mathematics achievement as the quitters type, and studentsâ mathematics learning achievement with the climbers type of learning results in a better achievement than studentsâ mathematics learning achievement with the quitters type.Keywords: Learning model,NHT, open-ended approach, conventional, mathematicâs learning achievement.